The Ideological Background of Japanese Expansionism, C. 1900 - Kleinschmidt, Harald (Studia Historiae Oeconomicae, 2023)
This paper examines the ideologies informing the expansion of Japanese rule at c. 1900. The core feature discussed is the idea of tenka (天下; literally translated: all under heaven), constituting the group of ruled in terms of a universalist indigenat (kokumin 国民), which allowed its expansion beyond the Japanese archipelago at government discretion. The concept of the universalist indigenat, having been tied to the Confucian perception of the world as a well-ordered and change-absorbing entity, conflicted with the European concept of the nation as a particularistically conceived type of group, tied to the perception of the world as a dynamic and largely unruly entity. During the latter third of the nineteenth and the early years of the twentieth century, some Japanese intellectuals came to appreciate the dynamism enshrined in the European perception of the world and worked it into established universalism. The fusion produced a powerful ideology of colonial expansion targeted primarily at East and Southeast Asia as well as the South Pacific. By contrast, European military strategists and political theorists, unaware of the Japanese strategic conceptions, expected that solely Russia formed the target of Japanese military expansion.